2013
DOI: 10.1130/l251.1
|View full text |Cite
|
Sign up to set email alerts
|

Upper-plate deformation in response to flat slab subduction inboard of the aseismic Cocos Ridge, Osa Peninsula, Costa Rica

Abstract: Along the Middle America Trench in southern Costa Rica, fl at slab subduction of the aseismic Cocos Ridge has uplifted and exposed the outer forearc, shortened the Térraba forearc basin sequence in the inner forearc (i.e., the Fila Costeña thrust belt), and uplifted the magmatic arc. The Osa Peninsula, an outer forearc high ~20 km inboard of the Middle America Trench and ~3 km to ~10 km above the plate interface at its trenchward edge, is deforming in response to variations in the bathymetry of the subducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 107 publications
(237 reference statements)
4
97
0
1
Order By: Relevance
“…ABRATIS and WÖ RNER (2001) assume that the Cocos Ridge has been subducting since 8 Ma, whereas other studies propose a much younger history, depending on the method used: 3.6 Ma (COLLINS et al 1995) and 3-2 Ma (MACMILLAN et al 2004). The studies of MORELL et al (2012),GARDNER et al (2013), andLONSDALE andKLITGORD (1978) support the assumption that the front edge of the ridge arrived at the trench later than 3 Ma. In the most recent modeling study, ZEU-MANN and HAMPEL (2015) derive an onset of Cocos Ridge subduction at *2 Ma.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…ABRATIS and WÖ RNER (2001) assume that the Cocos Ridge has been subducting since 8 Ma, whereas other studies propose a much younger history, depending on the method used: 3.6 Ma (COLLINS et al 1995) and 3-2 Ma (MACMILLAN et al 2004). The studies of MORELL et al (2012),GARDNER et al (2013), andLONSDALE andKLITGORD (1978) support the assumption that the front edge of the ridge arrived at the trench later than 3 Ma. In the most recent modeling study, ZEU-MANN and HAMPEL (2015) derive an onset of Cocos Ridge subduction at *2 Ma.…”
supporting
confidence: 63%
“…The Costa Rican part of the island arc can be subdivided into a northern and a southern arc segment (SEYFRIED et al 1991). The southern Costa Rican arc segment is influenced by flat subduction of the Cocos Ridge (CORRIGAN et al 1990;GARDNER et al 2013), which results in deformation and uplift on the upper-plate forearc (MORELL et al 2008(MORELL et al , 2012 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LaFemina et al (2009 suggested that the collision of the Cocos Ridge contributes to the northwestward motion of the forearc sliver. The buoyant, thickened crust of the Cocos Ridge acts as an indenter (Gardner et al, 2013) and arc-parallel forearc motion, as well as relative (north)eastward motion of the Panama-Chocó block represents tectonic escape (Kobayashi et al, 2014). Phipps Morgan et al (2008) noticed that the Motagua fault zone at present does not crosscut the Central American forearc and does not continue towards the Central American trench.…”
Section: Central Americamentioning
confidence: 97%
“…The seafloor offshore the Osa Peninsula stands $2.5 km higher than the surrounding seafloor [Barckhausen et al, 2001;Walther, 2003], due to the subduction of the aseismic Cocos Ridge, a 200 km wide and 1000 km long seamount chain formed at the Galapagos hot spot [Johnson and Lowrie, 1972;Werner et al, 2003] on the eastern edge of the Cocos Plate. The subduction of the buoyant Cocos Ridge has affected the upper plate structure, causing erosion of the outer forearc and the uplift of the Osa Peninsula and the Quepos region [Gardner et al, 1992[Gardner et al, , 2013Fisher et al, 1998;Sak et al, 2004].…”
Section: Introductionmentioning
confidence: 99%